2008
DOI: 10.1063/1.2916705
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stable thermoelectric Zn4Sb3 by zone-melting synthesis

Abstract: High-temperature thermoelectric properties of the double-perovskite ruthenium oxide (Sr1−xLax)2ErRuO6 J. Appl. Phys. 112, 073714 (2012) Thermoelectric properties of n-type Mn3−xCrxSi4Al2 in air J. Appl. Phys. 112, 073713 (2012) Thermoelectric effect in a graphene sheet connected to ferromagnetic leads J. Appl. Phys. 112, 073712 (2012) Thermoelectric properties of p-type Bi0.5Sb1.5Te2.7Se0.3 fabricated by high pressure sintering method J. Appl. Phys. 112, 073708 (2012) Dimensional crossover of charge dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 14 publications
(11 reference statements)
0
49
1
Order By: Relevance
“…1, is stable from 250-673 K. 13 A multitude of synthetic routes have been employed to produce b-Zn 4 Sb 3 , including quenching from the melt, 7,14,15 mechanical alloying of the elements, 13 flux-growth, 16 zone melting, 17 reactive hot-pressing, 18 sinter-forging 19 and gradient freeze methods.…”
mentioning
confidence: 99%
“…1, is stable from 250-673 K. 13 A multitude of synthetic routes have been employed to produce b-Zn 4 Sb 3 , including quenching from the melt, 7,14,15 mechanical alloying of the elements, 13 flux-growth, 16 zone melting, 17 reactive hot-pressing, 18 sinter-forging 19 and gradient freeze methods.…”
mentioning
confidence: 99%
“…[5] Iversen and co-workers reported the instability of the material even below 500 K with formation ZnSb, ZnO and elemental Sb as degradation products. [11] An onset temperature of 469 K was reported by Erk et al in the study of metastable nanocrystalline Zn 4 Sb 3 . [12] It has been shown that β-Zn 4 Sb 3 synthesised by thermal quenching decomposes very substantially when heated in atmospheric air, [11] whereas material synthesised by zone melting exhibits a remarkable stability.…”
Section: Introductionmentioning
confidence: 85%
“…[11] An onset temperature of 469 K was reported by Erk et al in the study of metastable nanocrystalline Zn 4 Sb 3 . [12] It has been shown that β-Zn 4 Sb 3 synthesised by thermal quenching decomposes very substantially when heated in atmospheric air, [11] whereas material synthesised by zone melting exhibits a remarkable stability. [11,13] Since the properties of β-Zn 4 Sb 3 synthesized by thermal quenching and by zone melting are different, it follows that the crystal structures and/or microstructure of the two materials must be different.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Just due to the complex Zn interstitial structure, Zn 4 Sb 3 possesses a higher ZT value to a large extent on accounts of lower lattice thermal conductivity which is less than 1 Wm·K. It is reported that Zn 4 Sb 3 can be fabricated using solid state reaction (Cadavid & Rodríguez, 2008), conventional quench method and zone-melting technique etc (Pedersen & Iversen, 2008). Only the Zn 4 Sb 3 fabricated by the last method is more thermal stable for more promising applications.…”
Section: Zn 4 Sbmentioning
confidence: 99%